Marked alteration of phosphoinositide signaling‐associated molecules in postmortem prefrontal cortex with bipolar disorder - Mizuki Hino; Yasuto Kunii; Risa Shishido; Atsuko Nagaoka; Junya Matsumoto; Hiroyasu Akatsu; Yoshio Hashizume; Hideki Hayashi; Akiyoshi Kakita; Hiroaki Tomita; Hirooki Yabe (Wiley, 2024)
Abstract Aim The etiology of bipolar disorder (BD) remains unknown; however, lipid abnormalities in BD have received increasing attention in recent years. In this study, we examined the expression levels of enzyme proteins associated with the metabolic pathway of phosphoinositides (PIs) and their downstream effectors, protein kinase B (Akt1) and glycogen synthase kinase 3β (GSK3β), which have been assumed to be the targets of mood stabilizers such as lithium, in the postmortem brains of patients with BD. Methods The protein expression levels of phosphatidylinositol 4‐phosphate 5‐kinase type‐1 gamma (PIP5K1C), phosphatidylinositol 4‐kinase alpha (PIK4CA), phosphatase and tensin homolog deleted from chromosome 10 (PTEN), Akt1, and GSK3β were measured using enzyme‐linked immunosorbent assays and multiplex fluorescent bead‐based immunoassays in the prefrontal cortex (PFC). Specifically, PTEN, Akt1, GSK3β, and PIP5K1C were measured in seven BD patients and 48 controls. Additionally, PIK4CA was analyzed in 10 cases and 34 controls. Results PTEN expression levels were markedly decreased in the PFCs of patients with BD, whereas those of Akt and GSK3β were prominently elevated. Moreover, patients medicated with lithium exhibited higher Akt1 expression levels and lower PTEN expression levels in comparison with the untreated group. Conclusion Our results suggest that the expression levels of Akt1/GSK3β and its upstream regulator PTEN are considerably altered.